Memaknai Konsep Hijrah Nabi Terdahulu dan Rasulullah SAW Berdasarkan Al-Qur’an - Prabowo, Yudhi (ANWARUL, 2022)
The understanding of hijrah which is generally understood today, is only understood as a transfer or physical such as a relocation as understood by the meaning of hijrah Rasulullah saw, and is not followed by a change in attitude and mentality. So hijrah must be understood ideally by looking at various references both from linear interpretations and books with comprehensive discussions both related to physical changes and attitudes. Hijrah is one of the important events that has a major influence, especially on the preaching of the Prophet Muhammad in upholding the Islamic religion and changing human morals. So the writer is interested in interpreting the concept of the migration of the previous Prophet and Rasulullah saw based on the Qur'an. This research study is entirely based on literature review or literature studies. Therefore, the nature of the research is library (Library Research). The data collected and analyzed all come from literature and other document materials, such as books, writings in journals, as well as in other media, which are relevant to the problem under study. Hijrah can also be said as an effort to leave forms of polytheism and towards monotheism (obedience) to Allah SWT. The implementation of hijrah is an obligation imposed on Muslims, it turns out that it has a big role in one's progress, among other things, as a symbol of obedience to Allah and His Messenger and as a process of cleansing the faith. Therefore the concept of hijrah is very important to be applied in the lives of Muslims